Clinical profile and lipid abnormalities in subclinical and overt primary hypothyroidism - Hiregoudar, Mrutyunjay B.; Mohanty, Pradeep Kumar; Tripaty, Sagnika; Kerketta, Amita; Soren, Uttam Kumar; Sukla, Sunil Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Overt and subclinical hypothyroidism, affects metabolism of lipids particularly that of cholesterol, low density lipoprotein and triglyceride. Hypercholesterolemia predisposes to atherosclerosis and thereby increases cardiovascular risks. Methods: Hundred patients of primary hypothyroidism of age more than 15 yrs were included. Five milliliters of venous blood was drawn in fasting state and serum obtained; thyroid function test (TFT) and fasting lipid profile were performed. Based on the TFT, patients were categorized as sub clinical or overt hypothyroidism. Clinical data, thyroid and lipid profiles obtained were analyzed and compared using statistical methods. Results: Seventy patients were females and thirty were males in the ratio of 2.3:1. Most common age group was 51-60years followed by 41-50years. Most common symptom was generalised weakness followed by weight gain, cold intolerance, constipation, hair loss, paraesthesia’s. Most common signs were myxoedema, delayed ankle reflex relaxation, dry and coarse skin, bradycardia, non-pitting peripheral edema, madarosis, pallor, goiter. Patients with Overt hypothyroidism had significantly higher serum levels of total cholesterol(249.1±31.7 mg/dl), Triglycerides (191.5±68.5 mg/dl) and LDL cholesterol(167.7±31 mg/dl) than the Subclinical hypothyroidism with total cholesterol(202±19.8),triglycerides(155.6±35) and LDL cholesterol(129±21.1) but HDL cholesterol level remains normal in both overt (44.0±4.7) and subclinical (43.1±4.4)hypothyroidism respectively. Conclusions: Patients with Overt hypothyroidism had significantly higher levels of Total cholesterol, Triglycerides (TG) and LDL cholesterol than the Subclinical hypothyroidism but HDL cholesterol level remains normal in both. So, concomitant estimation of lipid profile in hypothyroidism patients is needed for early intervention and prevention of cardiovascular morbidity and mortality.